Shear deformation and failure modes of the GFRP reinforced concrete beams without stirrups - Kaszubska, M. (2018)
The various shear-transfer actions due to: aggregate interlock effect, dowel action of the flexural reinforcement, the uncracked concrete in the compressive zone and the direct strut action for the point load close to the support, may provide different crack pattern in the shear span of the concrete beams without stirrups. The aim of this paper is to investigate the shear failure mechanisms in T-shape, single span and simply supported beams exclusively reinforced with longitudinal glass fiber reinforced polymer (GFRP) bars. The research of concrete beams flexurally reinforced with GFRP bars without stirrups indicated the possibility of occurring, besides the conventional shear-compression failure mode, another type of failure governed by the loss of bond between the ordinary reinforcement and concrete. Usually the critical shear crack in RC beams without stirrups develops through the theoretical compression strut preventing a direct transfer of the shear force to the support. The main parameter affecting the crack pattern and the shear strength of the beams is the shear span to depth ratio. However, the test results presented in this paper showed the formation of an arching effect due to the bond losing between the GFRP flexural reinforcement and concrete. This failure mode revealed unexpected critical crack pattern and failure mode. Digital image correlation (DIC) technique was used to better capture and analyse the cracking process up to the formation of the shear failure crack